Liquefaction potential analysis using the Tsuchida method and correlation of Relative Density (Dr) − D50 at Padang Beach - Andriani; Afifa Mifta; Yoriadi Didi; Shubhi Nurul Hadie Muhammad; Ahmad Fauziah (E3S Web of Conferences)
Indonesia’s seismic activity necessitates careful consideration of earthquake risks in construction projects, as seen in the 2009 Padang’s Earthquake with high sand content and water table near the coast. The test was carried out based on the gradation of soil grains through sieve analysis testing using the Tsuchida boundary and relative density testing by analyzing the correlation value between Dr and D50. The accelerations used in this test are 0.3g and 0.6g. Soil classification according to the AASHTO (American Association of State Highway and Transportation Officials) system, the type of sand on the beach is A-3 (fine sand), and according to the USCS (Unified Soil Classification System) system, all samples are classified as SP (Poorly-graded sand). With Cc (Coefficient Curvature) 2.436-1.975 and Cc (Coefficient Uniformity) 1.106-0.939. 0.3g Relative density ranges between 7-59%, and 0.6g ranges between 5-41%. Diameter passes 50% ranges between 0.187-0.408 mm. The Tsuchida boundary analysis and the Dr-D50 correlation retrieved similar results. Tsuchida analyses grain gradation, while Dr-D50 examines cyclic load and settlement for specific grain size, affecting liquefaction potential. One sample liquefied at 0.3g, while all samples liquefied at 0.6g. Due to a smaller diameter at 50% pass, it was indicating higher liquefaction potential.